Legal Sociology Approach: A Critical Study on Understanding the Law - Kaharuddin Kaharuddin (Veteran Law Review, 2023)
The need for legal certainty as progress and change in societal life. This article seeks to provide a description of legal practices in society that emphasizes a legal sociology approach to comprehending the laws, whether they are appropriate, different from or even at odds with the laws in the law book, or unwritten laws that are accepted as legitimate by society. This change has continued since antiquity, modern times, and even this age of civility or globalization.  There are many approaches and methods or approaches that can be used in building justice, including in the sociology of law approach.  Studies related to the method approach have recently experienced a dynamic development along with the needs and demands of the community. Theoretical studies and empirical research seek to answer various problems about the effectiveness of the work of law in the entire institutional structure of law in society. This legal sociology approach expects to describes the state of society complete with interrelated social structures and symptoms. It is used because the normative goal of the law is to have a good balance in society, the process of law is in the society itself, thus it can be said that society is the source of law, and the law cannot be separated from the social environment. It emphasizes the study of the relationship between law thinking and its social base and does not see the law as an esoteric area. The study of legal sociology using various approaches may give a positive contribution in understanding and developing law products and build a guaranteed life in accordance with applicable laws and regulations as well as community compliance with the law.